(untitled) (International relations and international law Journal, 2025)
This article examines the influence of cultural identity on the formation of the foreign policy of the Republic of Kazakhstan. Special attention is paid to initiatives aimed at strengthening national identity through international cooperation, and the prospects for the development of cultural diplomacy as an instrument of foreign policy influence are analyzed. The challenges facing Kazakhstan in the context of globalization and multilevel identity are also considered. The cultural identity of a nation is an important aspect that shapes its political, social, and economic structures. In the context of globalization, when culture becomes an object of exchange and mutual influence, countries face the task of preserving and promoting their identity in the international arena. It is the country’s "soft power" that can and should become one of the main elements of strengthening Kazakhstan’s international image at the global level, positioning itself as a responsible actor in regional and global politics. In this context, cultural identity should contribute to the achievement of the republic’s foreign policy goals Kazakhstan, as a multinational state, implements its foreign policy taking into account cultural aspects, which makes it possible to strengthen national identity. This article examines examples of the development of Kazakhstan’s cultural identity through its foreign policy. Key words: Republic of Kazakhstan, cultural identity, foreign policy, globalization, national interests, diplomacy, multinational society, geopolitics, intercultural dialogue.